Blue light emitted from digital devices - impact on our sleep - Justyna Kurek; Anna Gadomska; Rafał Gorzyński; Justyna Molczyk-Sieńczak; Michał Garstka; Hanna Dominik; Zuzanna Czudy; Wojciech Pawęska; Jan Radwański; Marika Polatowska (Kazimierz Wielki University, 2023)
Introduction: Today the use of digital devices is widespread in society. It has been observed increased frequency of sleep disorders occurring in the population in every age group. Scientists, concerned about the scale of the problem, have become interested in the effects of blue light emitted by the displays of digital devices, on sleep. Purpose of the work: The aim of the study is to answer the question whether a blue light emitted by digital devices affects sleep and to indicate the potential prevention of sleep disorders resulting from the use of digital devices. Materials and methods: A literature review was performed in the PubMed database using the keywords: blue light exposition; sleep quality; insomnia; light emitting diode; electronic device. Summary: Blue light emitted by various digital devices affects sleep by shortening and deteriorating the quality of sleep, falling asleep later, exacerbating feelings of sleep deprivation and increasing feelings of fatigue. Scientists have identified a couple of possible mechanisms to explain this phenomenon. There is a method that allows to reduce the negative effects of using various electronic equipment, without having to limit the length or set a rigid time frame for their use. Due to the increasing problem of sleep disorders and new habits among the society, scientists point out the need to monitor the discovered impact of blue light on sleep.